Determination of Work Motivation and its Implication on Employee Performance Secretariat of Kpu Se-Province Jambi - Roni, Khairun A; Moein, Anoesyirwan; Effendi, Nur Ika (International Review of Management and Marketing, 2018)
The problem of this research is what factors influence work motivation and its implications for the performance of the staff of the KPU Secretariat in Jambi Province, while the purpose of this study is to find out and analyse determinants of work motivation and its implications for the performance of employees of the KPU Secretariat throughout Jambi Province both partially and jointly. The research method used is descriptive and verification. Population the study was all employees of the KPU Secretariat throughout Jambi Province, with the number of samples research of 200 respondents taken by proportional random sampling technique. Data collected through research instruments to test the validity of research instruments, researchers used the KMO (Kaiser-Meyer-Olkin) technique, and to test reliability instrument with Alpha Cronbach. While the analytical technique used is Structural Equation Model (SEM). The results show that the work environment, work competence and work discipline has a positive and significant effect on work motivation both partially or simultaneous. The dominant variable that influences work motivation is work environment. As for the contribution of the work environment variables, work competencies, and work discipline to work motivation is 58% and the rest is contributed by other variables which are not examined. Furthermore, partially and together exogenous variables and motivational variables work as a mediating variable has a positive and significant effect on performance KPU Secretariat of employees throughout Jambi Province with a contribution of 86%, while the rest is contributed by other variables that are not examined. The dominant variable affecting employee performance is work motivation with a dimension of need for affiliates that can improve the performance of the KPU Secretariat employees in Jambi Province. Managerial implications are explained in this study that work motivation is within improving employee performance is partially mediating specifically for the work environment and discipline of work, whereas work competence directly affects employee performance and need to be considered and improved in improving employee performance at the KPU Secretariat All Jambi Province. Keywords: Work Environment, Work Competence, Work Discipline, Work Motivation, Employee Performance JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7166